2020
DOI: 10.1038/s41522-020-00138-8
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary trajectories of P. aeruginosa in biofilm and planktonic growth modes exposed to ciprofloxacin: beyond selection of antibiotic resistance

Abstract: Ciprofloxacin (CIP) is used to treat Pseudomonas aeruginosa biofilm infections. We showed that the pathways of CIP-resistance development during exposure of biofilms and planktonic P. aeruginosa populations to subinhibitory levels of CIP depend on the mode of growth. In the present study, we analyzed CIP-resistant isolates obtained from previous evolution experiments, and we report a variety of evolved phenotypic and genotypic changes that occurred in parallel with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 44 publications
(58 reference statements)
3
35
3
Order By: Relevance
“…Cross-resistance to β-lactam antibiotics was associated with mutations in genes involved in cell wall recycling ( ftsZ, murG ) and could also be explained by mutations in TCA cycle genes ( sdhA ) and genes involved in arginine catabolism. Interestingly, the set of identified mutated genes overlaps with a large number of pathoadaptive genes previously reported in P. aeruginosa isolates from CF patients [ 304 ]. Furthermore, pyomelanin-resistant mutants frequently coexist with other morphotypes in CF patients [ 326 ].…”
Section: Genomic and Phenotypic Approaches To The Study Of mentioning
confidence: 90%
“…Cross-resistance to β-lactam antibiotics was associated with mutations in genes involved in cell wall recycling ( ftsZ, murG ) and could also be explained by mutations in TCA cycle genes ( sdhA ) and genes involved in arginine catabolism. Interestingly, the set of identified mutated genes overlaps with a large number of pathoadaptive genes previously reported in P. aeruginosa isolates from CF patients [ 304 ]. Furthermore, pyomelanin-resistant mutants frequently coexist with other morphotypes in CF patients [ 326 ].…”
Section: Genomic and Phenotypic Approaches To The Study Of mentioning
confidence: 90%
“…Previous studies showed that acquired mutations conferring beneficial traits such as antibiotic resistance will dominate the populations when exposing biofilm bacteria to high concentrations of antibiotic [ 37 ]. Therefore, the enrichment of the hyperbiofilm rpoS mutation variants could have been achieved due to their enhanced resistance to imipenem.…”
Section: Resultsmentioning
confidence: 99%
“…The double mutant NfxB:Leu62fs/PilW:Ala164fs expanded to ~85% of the population on Day 3 and provided a genetic background for the appearance of the three GyrA mutant variants on Day 4 (Figure 2c, Supplementary Table 2D). The loss of type IV pili has been observed previously under CIP stress in P. aeruginosa (79). While the mechanistic rationale for this class of events remains unclear, it was hypothesized that the loss of type IV pili, known receptors for filamentous phages implicated in chronic infection, contributes to resistance against superinfection and lysis under ciprofloxacin stress (80).…”
Section: Additional Low Frequency Mutations Potentially Upregulating Another Multidrug Efflux Pumpmentioning
confidence: 88%